Hubungan Status Gizi dengan Kualitas Hidup Lansia di Posyandu Desa Tegal Sari Kecamatan Pante Ceureumen - Laila Apriani Hasanah Harahap; Safrida Safrida; Khairunnas Khairunnas; Adico Notareza Aulia (Jurnal Gizi dan Kuliner, 2023)
People over the age of 60 are considered elderly. Aging is not a sickness, but rather a process that causes the body's resilience to internal and external stimuli to gradually deteriorate. Physical difficulties, such as weakening, are a common occurrence in the aged. Anatomically and functionally, your nutritional status can deteriorate if your physical condition and function deteriorate. The elderly's quality of life is harmed by inadequate or high nutritional status. The purpose of this study is to discover the link between nutritional status and the quality of life of the elderly at the Pante Ceureumen Community Health Center. A correlational quantitative design with a cross-sectional method is used in this study. According to the research inclusion criteria, 70 respondents were identified using the sequence nonprobability sampling approach. Anthropometric measures and questionnaires were utilized to collect data. Kendall's tau test was utilized in bivariate data analysis. According to the findings, the nutritional status was 61.5% poor, 38.5% normal, 64.2% poor, and 35.8% good. This study finds that nutritional status and the quality of life of the elderly in Poshandu Tegal Sari have a substantial relationship. Keywords: elderly, nutritional status, quality of life